A Note on the Logic of Worldly Ground. (March 2015) - Krämer, Stephan; Roski, Stefan
Abstract : In his 2010 paper 'Grounding and Truth‐Functions', Fabrice Correia has developed the first and so far only proposal for a logic of ground based on a worldly conception of facts. In this paper, we show that the logic allows the derivation of implausible grounding claims. We then generalize these results and draw some conclusions concerning the structural features of ground and its associated notion of relevance, which has so far not received the attention it deserves.